Derivation of economic values for production traits in aquaculture species. Issue 1 (December 2017) - Janssen, Kasper; Berentsen, Paul; Besson, Mathieu; Komen, Hans
Abstract Background In breeding programs for aquaculture species, breeding goal traits are often weighted based on the desired gains but economic gain would be higher if economic values were used instead. The objectives of this study were: (1) to develop a bio-economic model to derive economic values for aquaculture species, (2) to apply the model to determine the economic importance and economic values of traits in a case-study on gilthead seabream, and (3) to validate the model by comparison with a profit equation for a simplified production system. Methods A bio-economic model was developed to simulate a grow-out farm for gilthead seabream, and then used to simulate gross margin at the current levels of the traits and after one genetic standard deviation change in each trait with the other traits remaining unchanged. Economic values were derived for the traits included in the breeding goal: thermal growth coefficient (TGC ), thermal feed intake coefficient (TFC ), mortality rate (M ), and standard deviation of harvest weight ( $$σ_{HW}$$ σ H W ). For a simplified production system, improvement inTGC was assumed to affect harvest weight instead of growing period. Using the bio-economic model and a profit equation, economic values were derived for harvest weight, cumulative feed intake at harvest, and overall survival. Results Changes in gross margin showed that the order of economic importance of the traits was:TGC, TFC, M, and $$σ_{HW}$$ σ H W . Economic values in € (kg production)−1 (trait unit)−1 were: 0.40 forTGC, −0.45 forTFC, −7.7 forM, and −0.0011 to −0.0010 for $$σ_{HW}$$ σ H W . For the simplified production system, similar economic values were obtained with the bio-economic model and the profit equation. The advantage of the profit equation is its simplicity, while that of the bio-economic model is that it can be applied to any aquaculture species, because it can include any limiting factor and/or environmental condition that affects production. Conclusions We confirmed the validity of the bio-economic model.TGC is the most important trait to improve, followed byTFC andM, and the effect of $$σ_{HW}$$ σ H W on gross margin is small.